Β-carboline-independent antidepressant-like effect of the standardized extract of the barks of Mimosa tenuiflora (Willd) Poir. occurs via 5-HT2A/2C receptors in mice. (July 2022) - Duarte-Filho, Luiz Antonio Miranda de Souza; Amariz, Isabela Araujo; Nishimura, Rodolfo Hideki Vicente; Massaranduba, Ana Beatriz Rodrigues; Menezes, Pedro Modesto Nascimento; Damasceno, Tauana Araújo; Brys, Ivani; Rolim, Larissa Araújo; Silva, Fabrício Souza; Ribeiro, Luciano Augusto de Araújo
Background: Depression is a psychiatric disorder with limited therapy options. Psychedelics are new antidepressant candidates, being the ayahuasca one of the most promising ones. A synergistic combination of N, N -dimethyltryptamine (DMT) and β-carbolines allows ayahuasca antidepressant properties. Another psychedelic and DMT-containing beverage is the jurema wine used religiously by indigenous people from Northeastern Brazil. Aims: To evaluate the antidepressant-like effect of standardized extract of Mimosa tenuiflora (SEMT), associated or not with harmine (β-carboline), in behavioral models of depression. Methods: The SEMT was submitted to (+) ESI-IT-LC/MS analysis for DMT quantification. To assess the antidepressant-like effect of SEMT, the open field (OFT), tail suspension (TST), and forced swim (FST) tests were performed. To verify the participation of serotonergic systems, the 5-hydroxytryptophan (5-HTP)-induced head twitch test was performed. Results: The content of DMT found in SEMT was 24.74 ± 0.8 mg/g. Yuremamine was also identified. SEMT presented an antidepressant-like effect in mice submitted to the TST and FST, independent from harmine, with no significant alterations on the OFT. The sub-dose interaction between SEMT and ketamine also produced an anti-immobility effect in the TST, with no changes in the OFT. SEMT potentiated the head twitch behavior induced by 5-HTP and ketanserin prevented its antidepressant-like effect in the TST ( p < 0.05). Conclusions: SEMT presented a harmine-independent antidepressant-like effect in mice submitted to the TST and FST. This effect occurs possibly via activation of serotonergic systems, particularly the 5-HT2A/2C receptors.